Miniplates Versus Reconstruction Plates in Vascularized Osteocutaneous Flap Reconstruction of the Mandible. Issue 2 (March 2019) - Zhang, Ze-Liang; Wang, Shuai; Sun, Chang-Fu; Xu, Zhong-Fei
Abstract : Purpose: The main aim of this article is to compare the complication rate associated with the use of miniplates versus reconstruction plates in vascularized osteocutaneous flap reconstruction of the mandible. Patients and Methods: The authors searched PubMed, Web of Science, EMBASE, Chinese BioMedical Literature Database (CBM), Cochrane Library, and clinicaltrials.gov up to September 2017 to identify studies that compared the complication rate of miniplates versus reconstruction plates in patients undergoing mandibular reconstruction. Two reviewers individually extracted the data and performed a quality assessment. Plate exposure, plate fracture/removal, infection, and overall complications were evaluated. Results: Five studies with 511 cases were included in our analysis. No significant difference was found between the groups. However, the reconstruction plate led to fewer overall complications and plate exposure postoperatively than did the miniplate. Conclusion: Our meta-analysis suggests that miniplates and reconstruction plates are suitable for mandibular reconstruction with a vascularized osteocutaneous flap.